The Effectiveness of STEM Integrated Handouts to Improve Students Creative Thinking Skills in Biotechnology Material - W Mentari; Abdurrahman Abdurrahman; T Jalmo (Universitas Muhammadiyah Purwokerto, 2019)
This study aims to know the effectiveness of STEM integrated handouts to improve students creative thinking skills in biotechnology material. The design used was nonequivalent pre-post control group design. This research was implemented in grade IX of SMPN 25 Bandar Lampung, Indonesia. The subject were 70 students divided into experiment class (N=35) and control class (N=35) with purposive sampling technique. The data collection was done by pretest and posttest for students creative thinking skills and students responses to the STEM integrated handouts. Based on the result, it were obtained that an average N-gain of experiment class was 0,64 greater than average N-gain of control class was 0,40. Both of class in medium category. Average N-gain of fluency was 0,50 and originality was 0,66 with medium category, then average N-gain of flexibility was 0,74 and elaboration was 0,79 with high category. The student responses showed almost all of the students agreed to the implementation of STEM integrated handouts lead to be interested and motivated in biotechnology material.